STUDY ON INOCULATION OF ECTOMYCORRHIZAL FUNGI ON PINUS KESIYA IN THAILAND - Khemnark, Choob (วารสารวนศาสตร์ไทย, 2022)
Ectomycorrhizal short roots of 4 commercial tree species in the pine and dipterocarp forests; Pinus kesiya, P. merkusii, Shorea obtusa, and Dipterocarpus obtusifolius were collected and isolated to prepare pure mycelial culture using the technique recommended by Marx (1969). Different techniques of inoculation were experimented on Pinus kesiya seedlings in different growing media and environmental conditions. The results showed that water suspension inocula was possible in semi-controlled environment. Pure mycelial culture, without leaching, by placing one tea spoon of inocula immediately beneath the root system of the transplanted seedlings gave better growth and survival than the controls. Seedlings inoculated with leached inoculum at 2 tea spoons per pot showed better survival and growth than the controls. Different growing media were tried in the pot culture at different amounts and the results showed that forest soil with pH 4.5 and high organic matter content was better than mixed soil and forest soil with pH 6.4 and low organic matter. Environmental conditions used in the studies consisted of three types of nursery; the glasshouse, the lathe house and the plastic net screen outdoor. The disadvantage of the lathe house and the plastic net screen was the amount of rainfall which is uncontrollable. It was observed that air temperature was rather high troughout the study; minimum temperature was 19.5 °C in January and maximum temperature was 39.0 °C in March. This high temperature was suspected to hinder ectomycorrhizal symbiosis. Field planting trial was carried out on the adversed site with erratic climatic conditions. The preliminary result showed that inoculated seedlings survived and developed better than the controls. All the controls died after outplanting for 4 months whilst the inoculated seedilings survived 18.18% after 3 years. Fruiting body has not yet appear to help identifying the ectomycorrhiza species.